If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(1 + -1x) = 6 (1 * 2 + -1x * 2) = 6 (2 + -2x) = 6 Solving 2 + -2x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -2x = 6 + -2 Combine like terms: 2 + -2 = 0 0 + -2x = 6 + -2 -2x = 6 + -2 Combine like terms: 6 + -2 = 4 -2x = 4 Divide each side by '-2'. x = -2 Simplifying x = -2
| 25=2x-y | | 4x+(2x+18)=180 | | 2x^2-4x-3=27 | | 2d=24+6d | | 8+5(z-4)=2(z+7) | | 7(3-x)=14 | | Py+aye=-4y+8 | | 3v-7v=5 | | 3x^2+23x-8.5=0 | | 8v-6v=4 | | 5(4d+8)=80 | | n(17+x)=34x-r | | 14a+20= | | y-5=28 | | 16x-3=86 | | 4(7t+1)-10=t-(t+5) | | 6(y+5)=-36 | | 3x-16=86 | | (2x^7-8y^8)(4x^6+6y^2)= | | 4n-7=45 | | 28+9x=258 | | 28+9=258 | | N+13.7=-6.3 | | 7u+4=4-7u | | 8-7n=34 | | 2k^2-7k=0 | | 5xm=d | | 7n+8=34 | | 0(t)=3.25t^2+-75 | | 6x-(3y)=15 | | 34-8=7n | | s(t)=3.25t^2-75 |